Mechanisms Linking Threat- and Deprivation-Related Childhood Adversity and Depression: The Biopsychosocial Model - Kemala, Cut N.; Jongsma, Marijtje L.A.; Hendrawan, Donny; Becker, Eni (UI Scholars Hub, 2023)
Childhood adversity involves a wide range of negative experiences that pose a serious threat to a child’s wellbeing. It has been consistently shown to predict (chronic) depression in subsequent stages of development, but mechanisms underlying the relationship are still less clear. Moving from a cumulative approach of lumping heterogeneous categories of childhood adversity to a dimensional approach of classifying negative experiences into two major dimensions (threat and deprivation) has facilitated the identification of specific processes by which childhood adversity can predict depression. This review aims to provide an integrative overview of how childhood adversity increases the risk for depression using the biopsychosocial framework. We will summarize findings from neuroimaging, behavioral, and social research. Recommendations for future research and preventions/interventions are also discussed.